Rancang Bangun Sistem Smart Parking Berbasis Mobile Menggunakan Mikrokontroler Esp32 - Saputra, Ardi; Zahfira, Dayanah; Sidabutar, Honey Christine; Irviantina, Syanti; Halim, Apriyanto (Universitas Methodist Indonesia, 2024)
Most universities manage parking for students and lecturers such as motorcycles and cars. But currently, there are many universities that still use manual methods, Mikroskil University is one of the private universities in Medan City which also still uses manual methods by checking the Vehicle Number Certificate by Mikroskil security officers. This inspection can result in a long queue at the exit of the parking area. In addition, students also have difficulty finding available parking spots in the parking area because there is no system that provides directions to see the availability of parking spots. Therefore, in this study a Smart Parking system was built using the application of the Internet of Things (IoT) system by creating a portal with a QR code scanner and adding a light sensor in each parking spot. The sensor testing results show that the light sensor is able to display the results according to the condition of the vehicle and then send the parking spot data to the application server, then based on the black box software testing, it is concluded that the software functionally runs well and produces results as expected. User testing conducted by students also shows the results as expected.